Industry structure and horizontal takeovers: Analysis of wealth effects on rivals, suppliers, and corporate customers - Shahrur, Husayn (Journal of Financial Economics, 2005)
We examine the wealth effects of horizontal takeovers on rivals of the merging firms, and on firms in the takeover industry's supplier and customer industries. Inconsistent with the collusion and buyer power motives, we find significant positive abnormal returns to rivals, suppliers, and corporate customers for the subsample of takeovers with positive combined wealth effect to target and bidder shareholders. Overall, our findings suggest that the average takeover in our sample is driven by efficiency considerations. However, we find evidence suggesting that horizontal takeovers increase the buyer power of the merging firms if suppliers are concentrated.